Manhaj Tafsir Lathaif Al-Isyarah Karya Imam Al-Qusyairi - Anindita Ahadah; Yovik Iryana; Eni Zulaih (LPPAIK Universitas Muhammadiyah Bandung, 2022)
Imam al-Qusyairi, who is known as one of the prominent figures of Sufi scholars, is also a muhaddits and commentator. Among his monumental works in the field of commentary is the book of commentary Lathaif al-Ikode. In this article the author will describe how a brief biography of Imam al-Qusyairi, a glimpse of the book of commentary Lathaif Al-Ikode, the characteristics of the interpretation of Lathaif Al-Ikode, a special manhaj of the interpretation of Lathaif Al-Ikode to examples from the book. This type of research is library research with a focus on research on the book of commentary Lathaif al-Ikode, using content analysis methods. The results of the study show that the manhaj or special procedure performed by Imam al-Qusyairi in the steps regarding the verses of the Qur'an in the Lataif al-Isign interpretation is that he always supervises the basmalah of words and letters. He uses Ma'rifah Al-Bathiniyah. He also quoted the opinion of his teacher. He did not include a discussion related to fiqhiyah issues, be it ahkam al-fiqhiah, qawaid al-ubudiyah or sanad-sanad. He also slipped an Al-Adabiy-style interpretation on the prohibition of the verses of the Qur'an Al-Karim. In determining the letter al-Muqatha'ah he emphasized that the verse cannot be known except for the All-Knowing One, namely Allah Subhanah Wa Ta'ala. But citing control - But about the letter al-Muqatha'ah. He also included syi'ir when examining the verses of the Qur'an to help organize in terms of language.